Reflections on the Qaṭna Letters TT1–5 (II): Hittite God-Napping in Syria - Torrecilla, Eduardo (Journal of ancient Near Eastern religions, 2023)
This article discusses and attempts to contextualize a few references to the practice of god-napping in the Qaṭna letters TT2–5 and in the Amarna letter EA 55. The references to god-napping in said letters enrich the debate on why the New Hittite Kingdom historiography, as opposed to the Old Hittite one, does not mention this practice, since the texts were probably written during or in the wake of Šuppiluliuma’s First Syrian War (ca. 1340). It is posited that the god-napping actions reflected in the texts concerning the fall of Qaṭna obeyed not only religious but also political and strategic motivations. God-napping was used whenever the New Hittite empire considered that it benefitted its strategic and cultic interests, even though it was no longer recorded by the Hittite historiography.